2013
DOI: 10.1088/0952-4746/33/4/823
|View full text |Cite
|
Sign up to set email alerts
|

Intake of radioactive materials as assessed by the duplicate diet method in Fukushima

Abstract: A large quantity of radioactive materials was released from Reactor-II of the Fukushima Daiichi Nuclear Power Plant (F-1 NPP). People living in the area affected by the release are concerned about internal exposures from the daily intakes of contaminated foodstuffs. In order to assess whether the people should be concerned, Co-op Fukushima (Consumer Co-operative in Fukushima Prefecture) conducted a broad survey of radiocaesium in daily meals for which local inhabitants voluntarily provided a set of duplicate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 9 publications
3
16
0
Order By: Relevance
“…These results reconfirm that the present levels of internal exposure found in people living in currently inhabited parts of Fukushima and in surrounding prefectures can be considered low [3][4][5]7]. This is different, however, from the perception of many parents raising children in the accident-affected areas, as the analyses of the questionnaire to the parents indicate.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These results reconfirm that the present levels of internal exposure found in people living in currently inhabited parts of Fukushima and in surrounding prefectures can be considered low [3][4][5]7]. This is different, however, from the perception of many parents raising children in the accident-affected areas, as the analyses of the questionnaire to the parents indicate.…”
Section: Discussionsupporting
confidence: 71%
“…However, most of the data accumulated and disseminated so far have consistently shown that the internal contamination for the majority of residents has fortunately been so low as to be undetectable [2]. These data include, for example, whole-body-counter surveys [3][4][5][6], duplicatediet studies [7], and the inspection of "all rice in all rice bags" harvested in Fukushima (2012-2014) [8].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that levels of internal radiation contamination are minimal amongst most residents of the affected areas in Fukushima, and that preventive food control measures are sufficient to avoid further internal radiation contamination in Fukushima [20]. The majority of inhabitants in the area appear to be consuming agricultural products classified as safe under the food monitoring system, and/or accessing foods from non-contaminated areas through modern food distribution systems.…”
Section: Discussionmentioning
confidence: 99%
“…Another study 15) Cs concentrations exceeding 1 Bq/kg. Even with the largest radioactive cesium value in this survey, daily consumption of such meals throughout a year gave an annual effective dose that did not exceed 0.1 mSv.…”
Section: Discussion and Future Tasksmentioning
confidence: 99%